The neutrophil-lymphocyte ratio and platelet-lymphocyte ratio predict left ventricular thrombus resolution in acute myocardial infarction without percutaneous coronary intervention - Sia, Ching-Hui (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
10.1016/j.thromres.2020.06.003